2020
DOI: 10.1186/s12872-020-01347-x
|View full text |Cite
|
Sign up to set email alerts
|

The hypotensive effect of salt substitutes in stage 2 hypertension: a systematic review and meta-analysis

Abstract: Background: Hypertension (HTN) is a ubiquitous risk factor for numerous non-communicable diseases, including cardiovascular disease and stroke. There are currently no wholly effective pharmacological therapies for subjects with HTN. However, salt substitutes have emerged as a potential therapy for the treatment of HTN. The aim of the present study was to assess the effect of salt substitutes on reducing systolic blood pressure (SBP) and diastolic BP (DBP), following a meta-analysis of randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
(85 reference statements)
0
9
0
3
Order By: Relevance
“…4,5,13,14 Although a systematic review and meta-analysis of other studies showed larger effects of salt substitution on blood pressure, all of these studies were of shorter duration than the current trial. 15 Incomplete adherence to use of the salt substitute, consumption of regular salt outside the home, and some use of a salt substitute in the control group probably attenu-ated the magnitude of the treatment effects in the current trial.…”
Section: Discussionmentioning
confidence: 90%
“…4,5,13,14 Although a systematic review and meta-analysis of other studies showed larger effects of salt substitution on blood pressure, all of these studies were of shorter duration than the current trial. 15 Incomplete adherence to use of the salt substitute, consumption of regular salt outside the home, and some use of a salt substitute in the control group probably attenu-ated the magnitude of the treatment effects in the current trial.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, in a salt-substitution trial conducted in Taiwan, the risk of CVD mortality was 41% less in those assigned to the potassium-enriched salt substitute group at 31 months (age-adjusted hazard ratio, 0.59 [95% CI, 0.37–0.95]) [ 104 ]. In previous meta-analyses, a significant positive effect of salt substitutes on SBP and DBP was reported [ 105 , 106 ]; however, in the present study, we included a larger number of related studies so as to conduct a stratified analysis on different factors, including age, baseline HTN status, follow-up duration, and sample size, which can influence the effect of the salt substitute on BP.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6]10,12,40 O consumo adequado de frutas e vegetais potencializa o efeito benéfico da dieta com baixo teor de sódio sobre a PA. Os substitutos do sal contendo cloreto de potássio e menos cloreto de sódio (30% a 50%) são úteis para reduzir a ingestão de sódio e aumentar a de potássio, apesar de limitações em seu uso. 42…”
Section: Sódio (Gr: I; Ne: A)unclassified